Spatiotemporal Metaphor: Vertical and Horizontal Axis of Time - Maria Tamarina Prawati (Journal of English Language and Culture, 2018)
Linguistic relativity holds an idea that structure of language affects the ways people conceptualize the world. It grows into two hypotheses which are linguistic relativism and determinism. The hypotheses explain how language and culture relate one another. The close relation is reflected through different system of sign, systematic conventional use of sounds or written symbol in different society (Crystal, 1971 and 1992) as what occurs in metaphor. Metaphor is not only written symbol but also thought and action rooted in our bodily experience (Yu, 1998, p.43). Therefore time as abstract concept should be best conceptualized through space. Keywords: metaphor, spatiotemporal metaphor, ego-moving, time-moving